The purpose of this post is to explain how KeYmaera X automatically proves reachability properties about differential equations of the form x' = f(x); and, in particular, equations whose solutions are exponential functions. My intended audience are people who are already familiar with the first 5 or 6 lectures of Foundations of Cyber-Physical Systems. This is about equivalent to the half-day KeYmaera X tutorials1.

Ultimately, the goal of this note is to explain how to find a useful differential ghost in order to prove a property about an exponential system such as x’=x.

Background and Motivation: Continuous Rechability Problems in KeYmaera X

Many control problems boil down to ensuring that a continuous system can only reach a safe subset of the overall state space.

For example, consider a model of an adaptive cruise control protocol. The engineering problem is to design a control algorithm that actuates a follower car’s acceleration such that the distance between the lead car and the follower car, denoted rx, is always strictly positive. In this example, the safe states are all states where rx > 0.

More generally, continuous reachability problems are expressed in Differential Dynamic Logic (dL) as formulas of the form:

P -> [{x' = f & H}]Q

where P, Q, and H are a first-order formulas of real arithmetic, and P -> [{X' = f}]Q is true iff every flow of the system x’ = f restricted to the set H and starting in the set P stays within the set Q.

Returning to the adaptive cruise control example, we can phrase our reachability problem as:

P -> [{rx' = rv, rv' = ra & rv > 0}] rx > 0

where rx is relative position and & rv > 0 is our syntax for restricting the flow of the system to sets in which rv > 0. There are many valid choices for P; for example:

rx > 0 & rv = 12 & ra = 0

In dL, we prove properties like this one by reducing the question to one that is expressible in a decidable fragment of first-order real arithmetic. In this case, we can integrate the system and arrive at a formula that looks something like:

P -> \forall t (t>=0->\forall s (0<=s&s<=t->ra*s+rv>0)->ra/2*t^2+rv*t+rx>0)

The truth of this formula is then established using a decision procedure for real arithmetic.

So why not just solve x’ = x?

Because model theory.

Unfortunately, not all systems have explicit closed form solutions expressible in terms of decidable fragments of Real Arithmetic. In particular, consider the equation x' = x, which has the solution e^t. Therefore, the arithmetic question corresponding to the reachability question P -> [{x' = x}] x > 0 looks something like:

P -> \forall t. e^t > 0

In general, we can’t simply appeal to a arithmetic decision procedure to answer questions of this form – the decidability of real arithmetic with exponentials remains an open problem.

In this post, I’ll explain how you can prove reachability properties about equations of the form x' = f(x) in KeYmaera X while staying with fragments of arithmetic that are known to be decidable.

Differential Ghosts

I assume as background familiarity with André Platzer’s lecture notes on differential ghosts, or a bit of experience with dL (e.g., having attended one of our KeYmaera X tutorials). The following review of ghosts is non-comprehensive, but might be a nice refresher.

dL’s differential ghost axiom augments a continuous system with a new equation that isn’t mentioned in the rest of the system:

[{ode & H}]P <-> ∃y.[{ode, y'=a*y+b & H}]P

The terms a and b may not mention y. Additionally, y must not occur anywhere in [{ode & H}]P. I.e., y' = a*y+b must by a linear system and y must be a fresh (new) variable.

Differential auxiliaries are a related concept that allow the post-condition to be re-stated in terms of the system’s new variable:

P <-> ∃y.G    G |- [{ode, y' = a*y+b & H}]G
--------------------------------------------- diffAux(y, a, b, G)
        P |- [{ode & H}]P

This proof rule appears a bit confusing at first. Seeing why this rule should be sound is not too subtle. P <-> ∃y.G establishes that G implies P for some choice of y, and G |- [{ode, y' = a*y+b & H}]G establishes that G remains invariant for any choice of y.

Seeing why this rule is helpful is a bit more subtle. I could waste some ink, but instead, I’ll just jump into examples!

Ghosts for Open Sets

In this section, we’ll consider various systems of the form x > 0 -> [{x' = f(x)}] x > 0.

Notice that we can’t prove anything about these systems using differential variants, and we can’t solve the system without turning one undecidable problem into another (for now, at least).

Example 1 x > 0 -> [{x' = -x}] x > 0

Before reading further, see if you can come up with a first order formula G that makes the premise of diffAux true; i.e., find a predicate G(x,y) that makes x>0 <-> ∃y.G true.

                     ------------------------------------- R
                            |- -xy^2 + 2xy(y/2) = 0
----------------- R  ------------------------------------- diffInd
x>0 <-> ∃y.xy^2=1    xy^2=1 |- [{x' = -x, y' = y/2}]xy^2=1
----------------------------------------------------------- diffAux(y, 1/2, 0, xy^2 = 1)
        x > 0 |- [{x' = -x}] x > 0

Hopefully you arrived at xy^2 = 1 by yourself. Notice that getting to a choice of y' = ay + b after fixing G is pretty mechanical; we just compute Lie derivatives of our choice of G:

(xy^2=1)' <-> (xy^2)' = 0         (def'n Lie operator =)
          <-> x'y^2 + x2yy' = 0   (def'n Lie operator *)
          <-> -xy^2 + x2yy' = 0   (because x' = -x)
          <-> y'(2xy) = xy^2
          <-> y' = xy^2 / 2xy
          <-> y' = y/2
          <-> y' = (1/2)y + 0     (just re-stating so it's clear a=1/2 and b=0)

The same proof generalizes nicely to monomials.

Example 2 x > 0 -> [{x' = -x^2}] x > 0

The choice of y changes slightly:

(xy^2=1)' <-> ... 
          <-> -x^2y^2 + x2yy' = 0
          <-> y' = x^2y^2 / 2xy
          <-> y' = (x/2)y + 0

Instead of giving the sequent calculus proof, here’s the KeYmaera X tactic:

implyR(1) ; DA4({`x*y^2=1`}, {`y`}, {`x/2`}, {`0`}, 1) ; <(
  QE,
  implyR(1) ; diffInd(1)
)

Some Proving Advice

At this point, you’ve already noticed that the choice of G and y' = ay+b are closely coupled. In fact, you only have to be creative once – there’s a systematic way of deriving a and b from a fixed G. This is true in the other direction as well.

I typically start with G, but as we’ll see with equilibrium points, it’s somethings helpful to move back and forth.

Ghosts for Equilibrium Points

In some sense, you would expect the proof of x=0 -> [{x' = -x}]x=0 to be trivial. But the proof of this property in dL (without extra proof rules like Khalil Ghorbal’s DRI) is a tough exercise. Before continuing, see if you can find some candidates for G and/or y'.

Here’s a choice for G: y>0 & x*y=0. Obviously, ∃y.x=0 <-> y>0 & x*y=0. However, a simple differential induction argument doesn’t suffice to establish the remaining subgoal:

y>0 & x*y=0 -> [{x' = -x}](y>0 & x*y=0)

We’ll need another ghost.

Notice that we already know how to prove

y>0 -> [{x' = -x}](y>0)

via a differential ghost argument. So let’s split this subgoal into two cases, which is a proof we can exploit using the boxAnd ([]^) axiom:

 (use open set approach)                            ...
-----------------------------           ----------------------------------
y>0 & x*y=0 |- [{x' = -x, y'=???}]y>0     y>0 & x*y=0 |- [{x' = -x}]x*y=0
--------------------------------------------------------------------------
        y>0 & x*y=0 |- [{x' = -x, y'=???}](y>0 & x*y=0)

Because we already know how to prove the first case, it makes sense to choose a value for y' = ax + b that makes the x*y=0 case prove by a differential invariance argument:

(x*y=0)' <-> (x*y)'=0
         <-> x'y + y'x = 0
         <-> -xy + y'x = 0
         <-> y' = xy/x = y

The proof for the case with the y>0 post-condition is the same as the proof for the close set examples.

Ghosts for Closed/Clopen Sets

The easiest way of dealing with properties of the form x>=0 is to think of them as a combination of a closed set and an equilibrium point:

x >= 0 <-> x > 0 | x = 0

The key to this techniques is to cut x > 0 | x = 0, case distinguish, and then use the following proof rule to rewrite the post-condition:

 |- Q -> P    G |- [a]Q
------------------------ G[]
       G |- [a]P 

E.g. by taking P as x >= 0 and Q as x > 0.

Here’s how that proof goes (starting after the cut):

          *             cont'd                      *             cont'd
    --------------  --------------------       -------------  -------------------
    |- x>0 -> x>=0  |- x>0 |- [{ode}]x>0       |- x=0 -> x>0  x=0 |- [{ode}] x=0
    ------------------------------------ G[]   ----------------------------------- G[]
            x>0 |- [{ode}] x>=0                     x=0 |- [{ode}] x>=0
-------------------------------------------------------------------------------- orL
                          x > 0 | x = 0 |- [{ode}] x>=0

For reference, here’s the tactic that does that (the open goals are skip‘d over):

implyR(1) ; cut({`x>0 | x=0`}) ; <(
  hideL(-1) ; orL(-1) ; <(
    generalizeb({`x>0`}, 1) ; <(skip, QE),
    generalizeb({`x=0`}, 1) ; <(skip, QE)
  ),
  hideR(1) ; QE
)

Conclusion

Proving reachability properties about exponential functions is one of the more difficult tasks for new KeYmaera X users. This may seem surprising because properties such as x=0 -> [{x'=x}]x=0 are so intuitively simple; however, given what we know about real arithmetic, perhaps this shouldn’t be so surprising after all.


Appendices

Appendix A Further Resources

Appendix B: Axiomatizing Differential Dynamics; Lie Derivatives

Differential invariants are the key piece of technology that allow us to obtain correct-by-construction solutions without resorting to a verified implementation of a fixed-point procedure. KeYmaera X axiomatizes continuous dynamical systems in terms of differential invariants and Lie derivatives.

A differential invariant is just a formula that remains true throughout the entire flow of an ODE. For example, suppose x=1 initially. Then:

  • x=1 is an invariant of {x'=0},
  • x>0 is an invariant of {x'=1}, but
  • x<1 is not an invariant of the equation {x'=-1} (because x<1 is not true in the first instant of the flow).

In KeYmaera X we can ask questions about invariants of differential equations using a formula of the form [ODE]inv where ODE is a (system of) differential equation(s) and inv is a formula describing the invariant. Notice that [ODE]inv is a formula, so it can be used with other logical connectives. For example, we can express the english prose “if x=1 initially then x>0 is an invariant of {x'=1}” using the formula x=1 -> [{x'=1}]x>0. Notice that x=0 -> [{x'=-1}]x<0 is also well-formed, but is false.

Evolution domain constraints allow us to assume invariants of a differential equation by restricting the flow of a differential equation to a particular domain. For example, if we define our dynamical system as the flow of x'=-1 restricted to the set x>0, then x>0 is, by force of definition, an invariant of the system. The KeYmaera X syntax for expressing that x>0 is an invariant of the system x'=-1 constrainted to x>0 is x=1 -> [{x'=-1 & x>0}]x>0.

Differential cuts are a way of embedding an invariant into the defintiion of a contiuous dynamical system. Think of cuts like lemmas – we first establish that I is an invariant of our system, and then get to assume throughout the rest of our proof that I is a component of the evolution domain constraint:

Γ |- [{ode & C}]I   Γ |- [{ode & C & I}]P
------------------------------------------ diffCut
        Γ |- [{ode & C}]P

Differential induction can be used to prove that a formula is an invariant of a differential equation:

[{x'=t}]P <-> [x':=t;]P'    (diffInd)

where P’ is the Lie Derivative of P. The definition of P' is straight-forward for terms:

(s+t)' = s' + t'
(s*t)' = s'*t + t'*s

and so on. The definition of unquantified formulas of real arithmetic is subtle (there are no typos on the following lines):

(f=g)'  <-> f' = g'
(f!=g)' <-> f' = g'
(f>g)'  <-> f' >= g'
(f<g)'  <-> f' <= g'
...

Explaining differential induction is beyond the scope of this blog post, but there is an excellent video with accompanying lecture notes for interested readers.


Change Log:

  • 2/26/2017: Fixed some typos and updated Bellerophon code samples to new ; syntax.

  1. In particular, I assume the reader is familiar with Differential Dynamic Logic and differential invariants/ghosts, but I’ll quickly review the basics. There are also a couple of appendices with incomplete explanations of various concepts.